Influência da produção docente em textos dissertativos no âmbito do PPGCI/UFPB: evidências a partir de referências e citações - Silva, Ruston Sammeville Alexandre Marques da (2012)
The graduate programs in Brazil are responsible for more than 90% of national scientific production. These programs are social networks in which the functions of production and consumption of scientific information are intrinsic. The research assumes that students of a program suffer intellectual influence, directly or indirectly, through interactions with their teachers, especially when there is a closer relationship, such as research groups, for example. Thus, we have as aim the analysis of quotes for teachers in the area of Information Science and characteristics of these productions, from dissertations of students of PPGCI / UFPB in the period 2009/2011. This is a documentary research, in which we use bibliometric techniques for data analysis, extracted from 34 dissertations, stored in the program´s site. There are 18 of line "Memory, Organization, Access and Use of Info" (Line 1) and 16 of the line "Ethics, Policy and Management Info" (Line 2). In three years (2009-2011) we find 195 references to 14 of the 18 faculty members of the current frame PPGCI / UFPB, eight and six of Line 1 and Line 2, respectively. Of the total, 98 are articles, 35 books, 11 book chapters, 17 theses, four dissertations, 23 in communication events, and 13 corresponding to the sum of research projects, reports research, summaries, and references that do not allow us to identify the medium used for communication. The transmission ratios, sharing and use of scientific information in the academic and more specifically in the context of PPGCI / UFPB were evident in references and quotes for teachers program, contained in dissertations analyzed. The intellectual influence faculty on the students was proven.